PENGARUH PROFITABILITAS, PELUANG PERTUMBUHAN DAN RISIKO KEUANGAN TERHADAP RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA) - B31111063, Hery Kurnia Yustanto (Jurnal Manajemen Update, 2016)
In recent years, automotive companies and its component had been increased significanly.. The growth of automotive sector attracts more investors to make investment, because the stock return for automotive sector has been steadely increasing every year. There are many factors affecting stock return , such as internal and external factors as well. This research is done to study internal factors to predict stock return such as  Profitability, Growth Opportunity, and Financial Risk. Population of this study was all the firms of automotive sub sector which are listed on Indonesian Stock Exchange for the periods 2010-2014. Sample was then  selected employing the purposive sampling technics, resulting  in 12 companies. Results in this study show that Profitability, measured by Return on Asset, affected  negativly and insignificantly on stock return in automative sector, whereas growth opportunity which was proxied by price to book value had positive and significant effect on stock return. At last,  financial risk proxied by Debt to Equity Ratio influenced positively but insignificant effect on stock return. Key Words : Stock return,Profitability, Growth Opportunity, Financial Risk,  Return on Asset, Price to Book Value, Debt to Equity Ratio (DER).